(3eNJUQ GdMSf GdMUjf ef cdGe SjO GdeQSdjfs - (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj , J (B833 (3g` s; (3eMeO Hf eMeO Hf eMeO Hf Ydj Hf jhSa, CHh GdNjQ, TeS GdOjf, GdYeQj GdOeTbqj Ke GdTjQGRj GdTGaYqj, GdTgjQ HGHf GdLRQj,(B833 (3g`s
(3ChdgG (B:s
(3hHYO aEfg deG cGf cJGHj GdMUf GdMUjf ef cdGe SjO GdeQSdjf MOGfj Ydi ENJUGQg aj gPg GdChQGb ef CUdg GdePchQ s
(3BNQgG (B:s
(3Gddge EfG fSCdc GdYGajI aj GdOfjG hGdBNQI hdjcf Pdc BNQ eG fYOOg ef YOg GdMUf GdMUjf ef cdGe SjO GdeQSdjf Ydjg GdUdGI hGdSdGe ef QH GdYGdejf s
(3GdMUf GdMUjf dGHf GdLRQj GfXQ cTa GdXfhf L (B1(3U` (B669s
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs